Early Assessment of Efficacy and Safety of Biologics in Pediatric Allergic Diseases: Preliminary Results from a Prospective Real-World Study - Lucia Caminiti; Francesca Galletta; Simone Foti Randazzese; Paolo Barraco; Stefano Passanisi; Antonella Gambadauro; Giuseppe Crisafulli; Mariella Valenzise; Sara Manti (2024)
Background: Despite the increasing interest in biologics for the management of allergic diseases, sparse real-world data are still available in the pediatric population. This study aimed to evaluate the early real-life efficacy and safety of omalizumab for patients with moderate-to-severe asthma and chronic spontaneous urticaria (CSU), and Dupilumab for patients with moderate-to-severe atopic dermatitis (AD). Methods: A prospective study enrolling children aged 6–18 years was designed to assess the efficacy and safety of biologic drugs at 16 weeks of treatment (T1). The effectiveness was measured using validated questionnaires (ACQ-5 for asthma, UAS7 for CSU, and EASI score for AD). Secondary outcome measures included reductions in inhaled corticosteroid (ICS) dosages, asthma-related hospitalizations/exacerbations, and quality of life (QoL) indicators (iNRS, sNRS, DLQI/cDLQI) for CSU and AD. Safety was expressed according to the descriptions of adverse events provided by EMA and FDA. Results: The study cohort consisted of eighteen children (mean age 12.9 ± 3.4 years). The omalizumab treatment significantly reduced ACQ-5 and UAS7 scores (p = 0.002 and p < 0.001, respectively). In patients with asthma, decreased ICS dosage and hospitalization/exacerbation rates were observed. QoL parameters significantly improved in CSU and AD patients. No severe adverse events were reported for either treatment. Conclusions: Our findings validate omalizumab and dupilumab as effective and safe therapeutic options for managing moderate-to-severe allergic diseases in children and adolescents.